The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/10934520500423238
|View full text |Cite
|
Sign up to set email alerts
|

Quality of “Sachet” Waters in the Cape Coast Municipality of Ghana

Abstract: To determine the quality of sachet water samples in the Cape Coast municipality of Ghana, random sampling procedures were used to collect 180 samples from 29 brands produced in the municipality from 1999 to 2004. For any particular year, each tested brand was sampled three times at intervals of not less than 2 weeks (usually monthly) between the months of March to June. Forty-five percent (45%) of the brands subjected to bacteriological examination contained coliform bacteria for one sampling period or another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 3 publications
2
30
1
Order By: Relevance
“…Several studies have reported poor bacteriologic or physiochemical quality of sachet water in Ghana over the past decade, [9][10][11][12][13][14][15][16][17][18][19] although a recent review of this literature through 2010 found that most sachet quality studies have suffered design flaws such as tiny samples sizes or egregiously nonrandom sampling. 3 The sachet water industry has also undergone significant transformation since the late 2000s because many cottage-industry players have been replaced by large corporate-type producers who are importing heavy industrial machinery to filter and process sachet and bottled water.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported poor bacteriologic or physiochemical quality of sachet water in Ghana over the past decade, [9][10][11][12][13][14][15][16][17][18][19] although a recent review of this literature through 2010 found that most sachet quality studies have suffered design flaws such as tiny samples sizes or egregiously nonrandom sampling. 3 The sachet water industry has also undergone significant transformation since the late 2000s because many cottage-industry players have been replaced by large corporate-type producers who are importing heavy industrial machinery to filter and process sachet and bottled water.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have documented coliform pollution of shallow wells and groundwater (Obiri-Danso et al 2009), rivers (Abdul-Razak et al 2009), rural and municipal domestic water supply (Ampofo 1997;Quagraine and Adokoh 2009), "sachet" and hand-tied drinking water (Dodoo et al 2006;Obiri-Danso et al 2003) in different parts of Ghana. As important as these studies are in revealing the health dangers associated with coliform bacteria, none of the papers confronted the issue through a well designed sampling programme to assess the sources of these pollutants in treated waters based on prevailing environmental conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Potable water scarcity in the region has become a "normal" problem for some decades now, and this compels the Ghana Water Company Limited to ration water. The inadequate water supply greatly affects productivity and has promoted the rampant water vending business of tanker and sachet water services with very doubtful water quality [22].…”
Section: Case Study and Data Collectionmentioning
confidence: 99%